Analysis of Cysteine Post Translational Modifications Using Organic Mercury Resin. (3rd October 2018) - Doulias, Paschalis‐Thomas; Gould, Neal S.
Abstract: The wide reactivity of the thiol group enables the formation of a variety of reversible, covalent modifications on cysteine residues. S ‐nitrosylation, like many other post‐translational modifications, is site selective, reversible, and necessary for a wide variety of fundamental cellular processes. The overall abundance of S ‐nitrosylated proteins and reactivity of the nitrosyl group necessitates an enrichment strategy for accurate detection with adequate depth. Herein, a method is presented for the enrichment and detection of endogenous protein S ‐nitrosylation from complex mixtures of cell or tissue lysate utilizing organomercury resin. Minimal adaptations to the method also support the detection of either S ‐glutathionylation or S ‐acylation using the same enrichment platform. When coupled with high accuracy mass spectrometry, these methods enable a site‐specific level of analysis, facilitating the curation comparable datasets of three separate cysteine post‐translational modifications. © 2018 by John Wiley & Sons, Inc.